Overbenefitting, underbenefitting, and balanced: Different effort–reward profiles and their relationship with employee well-being, mental health, and job attitudes among young employees - Li, Jie; Kaltiainen, Janne; Hakanen, Jari J. (Frontiers in Psychology, 2023)
We aimed to identify different, both balanced and imbalanced, effort–reward profiles and their relations to several indicators of employee well-being (work engagement, job satisfaction, job boredom, and burnout), mental health (positive functioning, life satisfaction, anxiety, and depression symptoms), and job attitudes (organizational identification and turnover intention). We examined data drawn randomly from Finnish population (n = 1357) of young adults (23-34 years of age) collected in the summer of 2021 with quantitative methods. Latent profile analysis revealed three emerging groups in the data characterized by different combinations of efforts and rewards: underbenefitting (16%, high effort/low reward), overbenefitting (34%, low effort/high reward), and balanced employees (50%, same levels of efforts and rewards). Underbenefitting employees reported poorest employee well-being and mental health, and more negative job attitudes. In general, balanced employees fared slightly better than overbenefitting employees. Balanced employees experienced higher work engagement, life satisfaction, and less depression symptoms. The findings highlight the importance of balancing work efforts with sufficient rewards so that neither outweighs the other. This study suggests that the current effort–reward model would benefit from conceptualizing the previously ignored perspective of overbenefitting state and from considering professional development as one of the essential rewards at work.